Synthesis and characterization of SiO2 particles for the development of a novel sun skin protector enriched with antioxidants. (2019) - Hernández, A.; Barrios, M.L.; Sánchez, M.L.
Abstract: This work is focused to study the influence of the reaction media, alkaline or acid media, the annealing temperature, and sonication treatment on size and morphology of silicon dioxide (SiO2 ) nanoparticles obtained by the sol-gel method. Structural and morphological characterization was performed by: Attenuated total reflectance – Fourier transform infrared (ATR-FTIR) and micro-Raman spectroscopy and scanning electron microscopy (SEM). The FTIR spectrum shows the absorption band assigned to the vibrational mode of Si-O-Si around 1080 cm -1 . The bands at 778 cm -1 and 472 cm -1 can be assigned to Si-O and O-Si-O stretching vibrations, respectively. The same bands are observed in the micro-Raman spectrum around 430, 493 and 708 cm -1, respectively. Such bands are more intense in the materials synthesized in alkaline media, suggesting an improvement in the crystal structure of the silicon oxide. This behavior confirms the presence of silicon dioxide (SiO2 ) in all prepared samples. The reaction in acid media produced particles with non-homogenous size and morphology. The material synthesized in alkaline media (IB, IBT) exhibits a surface morphology composed of nanoparticles spherical shape (average size = 100-250 nm). The sonication treatment further generated cluster-like nanoparticle agglomeration. Starting with the results, we corroborated the formation of SiO2 nanoparticles with potential morphological properties for their use as an active ingredient in sunscreens. Thus, research is aimed at the generation of new SiO2 nanomaterials for their evaluation as potential photoprotective physical agents, by modifying its morphological properties.